Causal associations of tea intake with COVID-19 infection and severity - Baranova, Ancha; Song, Yuqing; Cao, Hongbao; Yue, Weihua; Zhang, Fuquan (Frontiers in Nutrition, 2023)
Tea ingredients can effectively inhibit SARS-CoV-2 infection at adequate concentrations. It is not known whether tea intake could impact the susceptibility to COVID-19 or its severity. We aimed to evaluate the causal effects of tea intake on COVID-19 outcomes. We performed Mendelian randomization (MR) analyses to assess the causal associations between tea intake (N = 441,279) and three COVID-19 outcomes, including SARS-CoV-2 infection (122,616 cases and 2,475,240 controls), hospitalized COVID-19 (32,519 cases and 2,062,805 controls), and critical COVID-19 (13,769 cases and 1,072,442 controls). The MR analyses indicated that genetic propensity for tea consumption confers a negative causal effect on the risk of SARS-CoV-2 infection (OR: 0.87, 95% confidence interval (CI): 0.78-0.97, P = 0.015). No causal effects on hospitalized COVID-19 (0.84, 0.64-1.10, P = 0.201) or critical COVID-19 (0.73, 0.51-1.03, P = 0.074) were detected. Our study revealed that tea intake could decrease the risk of SARS-CoV-2 infection, highlighting the potential preventive effect of tea consumption on COVID-19 transmission.